A methodology for phenomenological analysis of cumulative damage processes. Application to fatigue and fracture phenomena. (September 2021) - Fernández-Canteli, Alfonso; Castillo, Enrique; Blasón, Sergio
Highlights: The evolution of damage phenomena is identified as stochastic sample functions. The methodology implies normalization and identification of sample functions as CDFs. Application to fracture and fatigue cases confirms the validity of the methodology. The complete cumulative damage process is reconstructed from only a partial record. Abstract: Sample functions, i.e., stochastic process realizations, are used to define cumulative damage phenomena which end into an observable terminal state or failure. The complexity inherent to such phenomena justifies the use of phenomenological models associated with the evolution of a physical magnitude feasible to be monitored during the test. Sample functions representing the damage evolution may be identified, once normalized to the interval [0, 1], with cumulative distribution functions (cdfs), generally, of the generalized extreme value (GEV) family. Though usually only a fraction of the whole damage evolution, according to the specific problem handled, is available from the test record, the phenomenological models proposed allow the whole damage process to be recovered. In this way, down- and upwards extrapolations of the whole damage process beyond the scope of the experimental program are provided as a fundamental tool for failure prediction in the practical design. The proposed methodology is detailed and its utility and generality confirmed by its successive application to representative well-known problems in fatigue and fracture characterization. The excellent fittings, the physical interpretation of the model parameters and the good expectations to achieve a complete probabilistic analysis of these phenomena justify the interest of the proposed phenomenological approach with possible applications to other cumulative damage processes.